Tren Positif Kolaborasi AI-Manusia: Survei Guru Musik Indonesia di Era Kurikulum Merdeka - Meyny S. C. Kaunang; Dinar Sri Hartati; Widyata Nikbert Sarayar; Waraney Josua Mongkau; Zelly Jeannie Lombeng; Jans George Mangare; Arie Tulus (JPKS (Jurnal Pendidikan dan Kajian Seni), 2026)
This study analyzes Indonesian music teachers' perceptions of the positive trend in human-AI collaboration in music composition learning during the Merdeka Curriculum era, addressing the local empirical survey research gap absent in prior studies. Employing a mixed-methods approach via systematic literature review (PRISMA-ScR) and Likert-scale survey on 5 music lecturers (N=5), findings reveal an overall mean score of 4.1 (1-5 scale) with 60-80% "Strongly Agree" dominance on AI's creative benefits (e.g., idea exploration mean 4.0), collaborative partner role (mean 4.0), and needs for training and ethical policies (mean 4.4). Despite the small sample, this indicates high optimism toward AI as a human creativity complement, alongside awareness of ethical risks like originality and authorship, aligned with TPACK and ADDIE models. The study contributes theoretically with empirical AI-TPACK evidence in the Indonesian context and practically via recommendations for AI literacy training, institutional policies, and survey expansion to bolster innovative Merdeka Curriculum implementation in national music arts education.